A remarkable permeability of canalicular tight junctions might facilitate retrograde, non-viral gene delivery to the liver via the bile duct. Issue 10 (28th June 2005) - Hu, J; Zhang, X; Dong, X; Collins, L; Sawyer, G J; Fabre, J W
Abstract : Aims: To establish the extent of retrograde bile duct infusion at an ultrastructural level, as a preliminary step before evaluating the efficacy of gene delivery to the rat liver via a branch of the bile duct. Methods: The extent of retrograde infusion into the biliary tree was established by light and electron microscopy, following infusion of 10 nm gold particles into the right lateral lobe. Canalicular permeability was further assessed by the infusion of a 67 kDa protein. For gene delivery, both naked DNA and a synthetic peptide vector system were evaluated. Because canalicular tight junction permeability can be compromised in damaged livers, both normal rats and rats recovering from the hepatotoxin D-galactosamine were studied. Results: The gold particles penetrated the peripheral one third of the hepatic lobules and, surprisingly, reached the space of Disse in normal rats. Equally surprisingly, blood levels of a 67 kDa protein were identical after bile duct infusion and portal vein injection. Gene delivery with peptide/DNA complexes was much more effective in rats treated with D-galactosamine. However, gene delivery with naked DNA was equally effective in normal and damaged livers. Localisation of gene expression showed a scattering of positive hepatocytes restricted to the right lateral lobe. Conclusions: Retrograde infusion into the bile duct advances well into the hepatic lobule and reveals a remarkable permeability of the canalicular or cholangiole tight junctions in normal rats. It is an effective approach for delivering genes to a small population (∼1%) of hepatocytes.